2021
DOI: 10.1111/jvim.16073
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic quantification of left atrial size in dogs with myxomatous mitral valve disease

Abstract: Background: In the absence of echocardiography, identification of cardiomegaly via thoracic radiography is a necessary criterion for classification of disease severity in dogs with myxomatous mitral valve disease (MMVD). Objective: Modified-vertebral left atrial size (M-VLAS) facilitates objective radiographic assessment of the left atrium (LA) in 2 dimensions and identifies LA enlargement more accurately than existing methods. Animals: Sixty-four dogs with various stages of MMVD and 6 control healthy dogs. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
71
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(87 citation statements)
references
References 39 publications
13
71
3
Order By: Relevance
“…18 The VLAS found in our study population is lower than the values proposed by Malcolm et al and more similar to those reported by Puccinelli et al 7,21 The same difference from data reported by literature can be observed for M-VLAS and RLAD. 8,9 It is interesting to report that the The main limitation for the current study was the small sample size.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…18 The VLAS found in our study population is lower than the values proposed by Malcolm et al and more similar to those reported by Puccinelli et al 7,21 The same difference from data reported by literature can be observed for M-VLAS and RLAD. 8,9 It is interesting to report that the The main limitation for the current study was the small sample size.…”
Section: Discussionmentioning
confidence: 88%
“…A correlation analysis between VHS, VLAS, M‐VLAS, RLAD, and TD to TW ratio was performed to determine whether chest conformation was responsible for variation in these radiographic parameters. To compare obtained VHS, VLAS, M‐VLAS, and RLAD measurements, the values from Malcolm's study expressed as median and interquartile range were converted to mean and standard deviation (2.07 ± 0.25 vertebrae); 7 the same was for M‐VLAS (2.6 ± 0.3 vertebrae) and RLAD (1.97 ± 0.57 vertebrae) 8,9,34 . A one sample t ‐test was then used to test whether the VHS, VLAS, M‐VLAS, and RLAD in our population of CKCS differed from the mean reference values proposed by literature 6–9,32 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations